Pengaruh Nanovaksin Berbasis Nanopartikel Hybrid Chitosan Terhadap Sel Darah Ikan Kerapu Cantang Yang Diinfeksi VNN - Gian Suryanatha Hartawan; Uun Yanuhar; Muhammad Musa; Heru Suryanto; Gunanti Mahasri; Apri Supii; Nico Rahman Caesar (Jurnal Ilmu Pertanian Indonesia, 2023)
Cantang grouper (Epinephelus sp.) is a fish with a high economic value and has been widely cultivated. VNN disase, caused by Betanodavirus infection, can lead to mass mortality of cantang grouper. Precautions considered effective in preventing Viral nervous necrosis (VNN) disease include vaccination. This study aimed to determine the effect of administering recombinant Chlorella vulgaris protein nanovaccine based on chitosan hybrid nanoparticles in increasing the immune response of cantang grouper infected with VNN. The study consisted of five treatments: K+ (cantang grouper infected with VNN), K- (healthy cantang grouper), T1 (healthy cantang grouper given 33 µl of nanovaccine and then challenged with VNN), T2 (healthy cantang grouper given 66 µl of nanovaccine and then tested with a VNN challenge), and T3 (healthy cantang grouper given 112 µl of nanovaccine and then tested with a VNN challenge). The parameters observed were haematology, nanovaccine Relative percent survival (RPS), and Survival rate (SR) levels. The study results showed that administering the nanovaccine increased the immune response of the fish, as indicated by an increase in haematology response, RPS, and SR in cantang grouper compared to the treatment without nanovaccine administration. The best dose of nanovaccine in this study is 33 µl. Keywords: fish disease, nanovaccines, virus, C. vulgaris, grouper